Comparative Role of Different Antibiotics for Non‐Perforated Acute Appendicitis a Meta-Base Histopathological Study - Shahabuddin, Muhammad Umar, Sohail Hameed, Afzaal Baig, Haseeb Ahmed, Hassan Zaheer, Naveed Shuja, Arslan Shuja, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The preferred method of treating appendicitis for more than a century has been appendectomy. Recent trials have challenged this theory. In patients with non-perforated appendicitis, this study evaluated the advantages and disadvantages of antibiotic treatment against appendectomy. Aims and objectives: Surgery vs. non-operative antibiotic treatment for acute non-perforated appendicitis. Study design: A meta-base histopathological study. Methodology: By using inclusion and exclusion criteria, all matched patients were chosen for the study and divided into two groups, group A and group B, using the closed envelop technique. All patients received an injection of injectable ceftriaxone 1 g and metronidazole 500 mg as part of an antibiotic prophylaxis regimen prior to surgery, while group A, patients received a single dosage of the same medications. Intravenous and oral antibiotic regimens, a second- or third-generation cephalosporin or ceftriaxone plus metronidazole injectable. The statistical software for the social science system (SPSS) version 17.0 was used for the statistical analysis. A (p≤0.05) value was used to denote a significant difference for all statistical tests. Antibiotics: Intravenous and oral antibiotic regimens (i) A second- or third-generation cephalosporin, or ceftriaxone plus metronidazole injectable (ii) single-agent regimens of amoxicillin-clavulanate. (iii) Fluoroquinolone or an advanced generation cephalosporin plus metronidazole, and amoxicillin-clavulanate. Practical Implications: In patients with non-perforated appendicitis, this study evaluated the advantages and disadvantages of antibiotic treatment against appendicectomy. In patients with clinically uncomplicated appendicitis, the decision between medicinal and surgical care is value and preference-dependent, indicating the need for a shift in practice towards collaborative decision-making. Results: Seroma was present in (12±0.01) of patients in group A and (20±0.02) of patients in group B; the (p≤0.05) value is very higher than Group-A, which is statistically insignificant. That implies that post-operative antibiotic medication does not lessen seroma development. In table-2 intra-abdominal abscess formation levels in group-A and Group- B were (7.2±0.02, 15±0.02) which indicated that antibacterial postoperative therapy was not effective as pre past- operative. That implies that antibacterial postoperative therapy does not lessen local site edema. People in both groups (16.2±0.01, 19±0.02) experienced pus discharge from the stitch line, and the p value is uncertain. Fever was seen in (6.5±0.01) of patients in group A and (10.2±0.02) of patients in group B; their p values were (P≤0.01 and P≤0.02) occasionally. Patients' length of hospital stays were shown that pre and post-surgery treatment was statistically significant than only post-surgery treatment. Conclusion: As a result, we can draw the conclusion from our study that, in cases of non-perforated appendicitis, carefully chosen and appropriately timed pre-operative antibiotics are sufficient in preventing Seroma formation, Intra-abdominal abscess formation, Local site edema, pus discharge from the stitch line, fever and stay in hospital. Post-operative antibiotics were not affect the rate of occurrence of the above mentioned variables. Keywords: Seroma formation, Intra-abdominal abscess formation, Local site edema, Pus discharge from the stitch line, Antibiotics. Appendicitis.